People, intangibles and digital transformation - Valter Vairinhos; Matos, F.; Edvinsson, L. (Knowledge, people, and digital transformation: Approaches for a sustainable future, 2020)
This chapter seeks to characterise the main issues of Digital Transformation (DT) and to relate this concept with National Intangible Capital (NIC), having in mind people’s attitudes and reactions to this transformation process, which is affecting the basic foundations of social life and civilisation. Previous technological revolutions replaced physical attributes of Man by the force of mechanical systems, and, later, machines were used to carry out repetitive, painful and dangerous tasks. With the present DT, intrinsic and noble characteristics of the human being, the mental characteristics, are being replaced or intended to be replaced by machines. This replacement is frequently made according to a logic that does not always put the Human Capital (HC) as the recipient and main beneficiary. Moreover, one of the main objectives of this work is to show that, despite the extraordinary complexity of social life and the relations between nations, technologies and science, DT is based on a small number of simple concepts, very stable over time and with universal meaning. This explains, in a great measure, the DT economic success and its potential for transforming all aspects of social, economic, political and cultural life. Furthermore, this is an illustration of the Intangible Capital (IC) or Artificial Intelligence (AI) multiplier effect.